Fatigue Assessment: Study Based on Physical Activity and Muscular Strength at Sedentary Workers - Arini, Shintia Yunita; Atmaka, Dominikus Raditya; Abdul-Mumin, Khadizah; Irwanto, Bian Shabri Putri; Agustin, Asri Meidyah (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Work fatigue is often a neglected problem because the symptoms are not specific and not visible directly to the naked eye. Occupational fatigue itself contributes more than 60% of all occupational accidents that occur in the workplace. The high rate of occupational fatigue that can contribute to work accidents is very interesting to be studied further related to the causal factors, including physical activity and muscular strength. The purpose of this study was to analyze the effect of physical activity and muscular strength with the incidence of fatigue in sedentary workers at Kalla Group located in Makassar, South Sulawesi. Method: The research is cross sectional study with samples in this study were sedentary workers who had relatively similar workloads and lifestyles which were then selected through simple random sampling calculations. This research uses ordinal regression statistical tests. Result: The test results obtained are p-value (p = 0.046) which means there is a significant relationship between fatigue and muscle strength, but there is no relationship between fatigue and exercise habits, no relationship between fatigue and smoking habits, no relationship between fatigue and staying up late and no relationship between fatigue and sitting time in a day on sedentary workers at Kalla Group, Makassar, South Sulawesi. Conclusion: Workers need to do light muscle stretching so that workers do not get tired easily when working in a static position for a long time and workers also need to adopt a healthy lifestyle.